Physiological Characteristics and Comparative Secretome Analysis of Morchella importuna Grown on Glucose, Rice Straw, Sawdust, Wheat Grain, and MIX Substrates - Cai, YingLi; Ma, XiaoLong; Zhang, QianQian; Yu, FuQiang; Zhao, Qi; Huang, Wei; Song, JiaXin; Liu, Wei (Frontiers in Microbiology, 2021)
Morels (Morchella sp.) are an economically important edible macro-fungi, which can grow on various synthetic or semi-synthetic media. However, the complex nutritional metabolism and requirements remain ill-defined. This study, based on the plant biomass commonly used in morels cultivation, assessed and compared the growth characteristics and extracellular enzymes of M. importuna cultivated on glucose, rice straw, sawdust, wheat grain, and a mixture of equal proportions of the three latter plant substrates. M. importuna could grow on all five tested media but displayed significant variations in mycelial growth rate, biomass and sclerotium yields on the different media. The most suitable medium for M. importuna was wheat-rich medium, followed by glucose, while rice straw and sawdust were the least suitable. A total of 268 secretory proteins were identified by LC-MS/MS detection. Functional classification and label-free comparative analysis of these proteins revealed that carbohydrate-active enzyme (CAZYme) proteins were the predominant component, followed by protease, peptidase and other proteins. Abundances of CAZYme proteins differed among the tested media, ranging from 64% on glucose to 88% on rice straw. The CAZYme classes of glycoside hydrolases and carbohydrate-binding module were enriched in the five secretomes. Furthermore, the enzyme activities of CMCase, lignase, amylase, xylase, pNPCase and pNPGase and relative expression of the corresponding genes were detected during continuous culture of M. importuna in MIX medium. The comprehensive data inferred that M. importuna had a weak ability to degrade lignocellulose but a strong ability to degrade starch. Specifically, in terms of the degradation of cellulose, the ability to degrade cellulose into oligosaccharides was much stronger compared with further degradation into monosaccharides, and this might be the speed-limiting step of cellulose utilization in M. importuna. In contrast, M. importuna had a strong ability to decompose various hemicellulose glycosidic bonds, especially α- and β-galactosidase. Only a very few lignin-degradation-related proteins and low abundance were detected, indicated a weak lignin degradation ability. Furthermore, the presence of lipase and chitinase implied that M. importuna was capable of decomposition of its own mycelia in vitro. The study provides key data that facilitates further understanding of the complex nutritional metabolism of M. importuna.